Que seulement de tes yeux tu regardes ...: étude structurelle de treize psaumes - Auffret, Pierre (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2003)
The author again presents a collection of studies examining the literary structure of the Psalms (in this case 9-10, 37, 46-48, 68, 78, 105, 106, 143) (cf. BZAW 235 and 289). The study starts by listing structural elements (recurrences of terms, phonetic similarities, synonyms, turns of phrase, oppositions) and working from these examines first the smallest structures, and then proceeds to larger and larger structures until the structure of the whole psalm has been revealed. It is thus possible to incorporate into the interpretation all the relationships inherent in the text itself, which thus